Graphic removal of water wave impact on the pool wall during the flip turn - Pereira, S. M.; Gonçalves, P.; Fernandes, R. J.; Machado, L.; Roesler, H.; Vilas-Boas, J. P. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: When the swimmer approaches the wall for the turn, part of the water volume displaced hits the wall before the swimmer`s contact, causing the acquisition of an "anticipatory" force curve (Lyttle, 2000; Roesler, 2002). The aim of the present study was to develop a graphical technique to remove the wave that precedes the contact of the swimmer with the wall during the front-crawl flip turn, characterizing and quantifying it. METHODS: A extensometric underwater force platform was used, and two video cameras were attached to record the contact and monitor the contact time of the swimmer`s feet on the wall. A male swimmer held 8 turns with maximum speed, but without touching the platform to characterize the wave kinetics. Afterwards, a sample of 17 swimmers performed 154 valid flip turns. To eliminate the wave signal interference in the force signal produced by the swimmer at the wall, a graphical solution was used during the signal processing performed using the Matlab software. Based on the trend of symmetry of the wave around its peak value, the program eliminated the water wave effect out of the original signal by reconstructing the curve from the time of the initial contact. RESULTS: The comparison of the impulse (time integral of the force / time curve) with and without the water wave effect showed, respectively, values of 314.48 ± 62.75, and 288.57 ± 51.79 Ns, pointing out a reduction of 10.87 % of the original force to time curve after the wave effect was removed. DISCUSSION: The comparison of the characteristics of the force to time curve of the wave produced by a swimmer during a flip turn, with and without touching the wall, support satisfactorily the solution proposed to remove the water wave effect from the swimmers` kinetics. It is accepted that the error associated with the wave data elimination with this procedure is not relevant, ensuring data integrity and increasing accuracy of the swimmer`s kinetics evaluation at the wall contact.